Artificial Intelligence Ethics and Maqasid al-Shariah in Islamic Religious Education for Malaysian Universities - Masruatus Saadah (Muaddib: Jurnal Pendidikan Agama Islam, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed educational practices worldwide, including Islamic Religious Education (IRE). While AI offers substantial opportunities to enhance learning effectiveness, personalization, and accessibility, its implementation also raises ethical concerns related to privacy, academic integrity, algorithmic bias, transparency, and the preservation of religious values. In the Malaysian context, where Islamic education plays a strategic role in shaping students’ moral and spiritual development, the integration of AI requires a framework that aligns technological innovation with Islamic ethical principles. This conceptual paper aims to develop a framework for AI ethics in Islamic Religious Education by integrating contemporary AI ethics principles with the objectives of Islamic law (Maqasid al-Shariah). Using a qualitative conceptual approach through an extensive review of literature on AI ethics, educational technology, Islamic education, and Maqasid al-Shariah, the study identifies key ethical dimensions relevant to AI implementation in IRE. The proposed framework encompasses the principles of transparency, accountability, justice, privacy protection, human dignity, and educational responsibility, supported by the Maqasid al-Shariah dimensions of preserving religion (hifz al-din), intellect (hifz al-‘aql), life (hifz al-nafs), wealth (hifz al-mal), and lineage (hifz al-nasl). The framework offers theoretical guidance for policymakers, educators, and higher education institutions in Malaysia to promote responsible AI adoption while maintaining Islamic values and educational objectives. The study contributes to the growing discourse on ethical AI in religious education and provides a foundation for future empirical investigations in Islamic educational settings.